Guided inquiry laboratory to improve research skills of prospective biology teachers - Zuhdan Kun Prasetyo; Djukri Djukri; Djohar Maknun (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study described guided-inquiry laboratory impact on increase in research skills of prospective biology teachers. Skill research indicators are designing, implementing, and reporting. This study was a non-equivalent control group design using experimental and control groups. Data were collected from 60 participants through observation of research skill indicators, namely designing, performing, and reporting then analyzed quantitatively-descriptively. The sample was selected using purposive sampling. The results confirmed that the guided-inquiry laboratory application has a more effective impact on improving research skills than ordinary learning. Each indicator of research skills (designing, performing, and reporting in the experimental class) meets the "Medium" category, while the "Low" category in the control class. This study concluded that the guided inquiry laboratory has a positive impact in improving the research skills of prospective biology teachers. This research provides a reference for teachers to explore the research abilities of their students.